Differing environmental drivers of settlement across the range of southern rock lobster (Jasus edwardsii) suggest resilience of the fishery to climate change. (14th October 2016) - Hinojosa, Ivan A.; Gardner, Caleb; Green, Bridget S.; Jeffs, Andrew; Leon, Rafael; Linnane, Adrian
Abstract: Temporal and spatial trends in settlement of the southern rock lobster, Jasus edwardsii, were examined to identify the influence of environmental variables over different spatial scales. Settlement data were collected from 1994 to 2011 along the Southern Australian and New Zealand coasts. We identified common settlement trends at a regional scale (100–500 km): the magnitude of settlement at sites from South Australia (SA) and Victoria (VIC) were similar, but different to sites in Tasmania (TAS). In New Zealand, three spatial regions were identified: northern (NNZ), middle (MNZ) and southern regions (SNZ). Higher settlement in SA, VIC and MNZ occurred in years with higher rainfall and storms in spring and El Niño conditions. In TAS and SNZ, higher settlement occurred during La Niña conditions. These results suggest that settlement over regional scales is modulated by oceanic processes, but outcomes vary between regions. At a local scale, a higher wave period and wind relaxation were relatively more important than the sea surface temperature (SST) in SA and VIC. In TAS, the current velocity also influenced the strength of settlement. However, much of the local settlement variability was not explained by the models suggesting that settlement in J. edwardsii is a complex process where larval behaviour, biological factors and oceanographic processes interact over different scales. The apparently complex processes affecting settlement showed that environmental conditions that reduced settlement strength in one region of the fishery often increased settlement strength in other regions. This could provide resilience to climate change at the stock level.